Influence of activation mode, fatigue, and ceramic interposition on resin cements' diametral tensile strength - Paula Nunes Guimarães PAES; Mauro Sayão de MIRANDA; Hélio Rodrigues SAMPAIO-FILHO; Lourenço CORRER-SOBRINHO
Abstract This study evaluated the influence of activation modes, on Diametral Tensile Strength (DTS) of dual cured resin cements subjected to a Mechanical Fatigue test (MF). Four dual-cured resin cements (RelyX UNICEM [U], RelyX ARC [A], ENFORCE [E] and Nexus 2 [N]) were activated by three different curing modes as follows: Self-Curing (SC), Dual Cure activation with photoactivation executed directly (DC) and Dual Cure activation with Photoactivation Through Porcelain (DCTP). After 24 hours, half of the sample was subjected to 30.000 fatigue cycles at 1 Hz frequency and 12 N load. Then, all specimens were subjected to DTS test in Instron Universal Testing Machine and data were analyzed by three-way ANOVA and Tukey's Test (5%). The results of DTS test means (MPa) and standard deviation, for each cement factor activated by SC, DC and DCTP was respectively: U (28.12 ± 5.29; 37.44 ± 6.49 and 40.10 ± 4.39), A (49.68 ± 8.42; 55.12 ± 5.16 and 63.43 ± 6.92), E (49.12 ± 3.89; 56.42 ± 8.88 and 56.96 ± 6.45) and N (61.89 ± 11.21; 59.26 ± 9.47 and 62.56 ± 10.93). Turkey's test indicated that DC is related to the highest DTS values; Nexus 2 DTS remained the same independently of activation mode and that the Porcelain disk interposition enhanced DTS only for RelyX ARC the ANOVA statistical test indicated that MF didn't alter the DTS values for all experimental groups. MF results clinical implication is that all cements tested exhibited, in an immediate loading, good cross linked bonds quality.